Titch. - Hutchins, Pat, 1942- (New York : Macmillan, 1971)
Nothing Titch owned amounted to much except the smallest thing of all--a seed.
1.5
K-3
K-3
School Library Journal
340
Keywords: Size -- Fiction; Brothers and sisters -- Fiction; Seed -- Fiction